How to marry Keanu Reeves in 90 days - Jackson, K. M. (Forever, 2021)
"Bethany Lu Carlisle is devastated when the tabloids report actor Keanu Reeves is about to tie the knot. What?! How could the world's perfect boyfriend and forever bachelor, Keanu not realize that making a move like this could potentially be devastating to the equilibrium of...well...everything! Not to mention he's never come face to face with the person who could potentially be his true soulmate -- her. Desperate to convince Keanu to call off the wedding, Lu and her ride-or-die BFF Truman Erikson take a wild road trip to search for the elusive Keanu so that Lu can fulfill her dream of meeting her forever crush and confess her undying love. From New York to Los Angeles, Lu and True get into all sorts of sticky and romantic situations, mimicking scenes from some of the most memorable Keanu blockbusters. Will Lu be able to find Keanu and convince him she's the one for him? Or maybe she'll discover true love has been by her side all along.."--